Space-time localization in problems with free boundaries for a nonlinear second-order equation - Berezovsky, A. A.; Mitropolskiy, Yu. A.; Shkhanukov-Lafishev, M. Kh. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For thermal and diffusion processes in active media described by nonlinear evolution equations, we study the phenomena of space localization and stabilization for finite time.